Pelatihan Penggunaan E-Learning Untuk Meningkatkan Literasi Digital Bagi Guru SMP Negeri 1 Gunungsindur - Oktovia, Oktovia; Afriani, Risma; Setiawati, Aini; H, Rizky Nurul; Marsam, Thoif; Sipahutar, Riana Puspita; Munali, Munali; Herawati, Mirna (Universitas Pahlawan Tuanku Tambusai, 2026)
Community service activities aim to make a real and meaningful contribution to society through the application of science, technology, and expertise to improve quality of life, solve social problems, and support community development and empowerment. Through a Participatory Action Research approach with a focus on training activities via webinars, the aim is to optimize the E-Learning platform effectively and increase student engagement in digital learning at SMP Negeri 1 Gunungsindur through three main stages: planning, implementation, and evaluation. The results of this activity show that the participants' knowledge and skills achieved an average of 78% (target 75%) with a participant satisfaction rate of 90%, indicating that the material and delivery methods are relevant and useful for teachers' needs. With increased digital literacy and teacher capabilities, schools can be better prepared to face modern educational challenges, including adapting to hybrid or distance learning.